Efectos de un programa de estimulación temprana en la socialización de los niños/as de 2 años de la I.E Inicial Particular Jorge Müller - Cordova Bardalez, Anllhel Arabella (2013)
The investigation has had by intention to undergo the effects of the Program of Early Stimulation in the socialization of the children and children of 2 years of age of the Educative lnstitution lnitial Individual of the Rioja city. The investigation is in level 111; causal relation with hypothesis, quantitative predominant analysis applied and also qualitative theoretician, of preexperimental design with pre test - pos test with a single group. The sample was constituted by 11 children'sof two years old in the Educative lnstitution lnitial Individual "Jorge Müller" of the City of Rioja in the 2011. The instruments of data collection test was a list of 1 collate of entrance (pre test) and a list of 1 collate of exit (post test). These instruments of investigation were validated by three experts, as it is considered in the list of credits of each instrument. After the analysis of results the socialízation of the children's of two years old of age of the Educative lnstitution was determined that Particular "Jorge Müller" of the City of Rioja in the 2011, has increased significantly with the application of the Program of Early Stimulation, being confirmed the alternating hypothesis.